Evaluasi Alih Fungsi Lahan Pertanian Menjadi Lahan Industri di Kabupaten Kendal Tahun 2014 - 2018 - Fitrian Adiyaksa; Prijono Nugroho Djojomartono, Ph.D. (Universitas Gadjah Mada, 2020)
Kendal Regency is an agrarian area with a percentage of agricultural land 54.57% of the total land area of 1,002.23 km2. With the government programs of construction of the Kendal Industrial Park (Kendal Industrial Park) which was built on an area of 2,700 hectares. Most of the land used for development of the Kendal Industrial Area is agricultural land. The purpose of this study was evaluated about the suitability of land use change from agricultural land into industrial land in Kendal Regency in period of 2014 to 2018 with the Kendal Regency Regional Spatial Plan in 2011 - 2031. The research method was quantitative. The method of data collection in this study was census about industry location permit and land use change permit in Kendal Regency from 2014 to.d. 2018. The data collection technique in this research was documents review about secondary data from related institutions. Data analysis techniques in this study were divided into spatial analysis and statistical analysis. The spatial analysis technique used Geographic Information System (GIS) concept, and used overlay method on digital maps. Statistical analysis used to produce information in tables and graphs. The results of this study indicate about the growth in period 2014 to 2018, the number of land use permits increase to 134 permits devide by 34 industry location permit with covering area about 732,792 m2 and 100 land use change permit with covering area equal 690,303 m2. In addition, about 91.18% of industrial location permits and 62% of land use change permits from agriculture into industries in accordance with the Kendal Regional Spatial Plan between 2011 to 2031.